2010
DOI: 10.1159/000320740
|View full text |Cite
|
Sign up to set email alerts
|

Extraordinarily Prolonged Disease Recurrence in a Granulosa Cell Tumor Patient

Abstract: Background: Granulosa cell tumors are rare sex cord stromal lesions that comprise approximately 3% of all ovarian neoplasms. The vast majority of granulosa cell tumors are considered indolent but in spite of aggressive management, delayed recurrence is of significant concern. Case Report: We describe a case involving a 67-year-old woman who presented with abdominal pain, bloody stools, and mild nausea. Following a CT scan of the abdomen and pelvis, a 19-cm pelvic mass was identified. Her prior medical history … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…On images, a large recurrent tumor can mimic a primary tumor originating from the liver, spleen and small intestine, or a primary retroperitoneal tumor. 25 28 Rha et al 6 reported that recurrent tumors are characterized as a relatively small number of discrete peritoneal or retroperitoneal tumors with an imaging appearance, which can vary from solid to cystic tumors. This study found that 7 of the 11 patients had 2 or more recurrent tumors.…”
Section: Discussionmentioning
confidence: 99%
“…On images, a large recurrent tumor can mimic a primary tumor originating from the liver, spleen and small intestine, or a primary retroperitoneal tumor. 25 28 Rha et al 6 reported that recurrent tumors are characterized as a relatively small number of discrete peritoneal or retroperitoneal tumors with an imaging appearance, which can vary from solid to cystic tumors. This study found that 7 of the 11 patients had 2 or more recurrent tumors.…”
Section: Discussionmentioning
confidence: 99%